Environmental Engineering Electronic Text (ENVETEXT). - Webb, Tony (Committee for University Teaching and Staff Development, 1997)
Final report of a Teaching Fellowship at The University of New South Wales. For this Fellowship, an electronic text was developed for an advanced undergraduate Environmental Engineering course. The text makes copious use of dynamic simulations using Word and Matlab software through which students can not only see all simulation details but can also develop solutions, add comments and import foreign material. The educational problem addressed is: how can a student grasp the principles of environmental science and technology more efficiently and in greater depth. With the traditional expository lecture style the student takes a passive role in which it is impossible to retain concentration for a full hour no matter how eloquent the delivery. Tutorials are far more effective because the student is then an active participant. With the aid of the electronic text the tutorial-style learning is used for newly-introduced material, not just for reinforcement. The prime target group is a class of engineering or science students in their third or final year although the material has also been used for postgraduate students with success.